2014
DOI: 10.17795/ijep20157
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Antimicrobial Extract from Elaeagnus angustifolia

Abstract: Background: According to ethnobotanical data, Elaeagnus angustifolia fruit has wound healing activity, anti-inflammatory effect and antifebrile prosperities. Objectives: This study was performed as to the best of our knowledge; there has been no scientific report on the characterization of antimicrobial effect of E. angustifolia extract. Materials and Methods: An aqueous extract of Elaeagnus angustifolia was prepared and antimicrobial activity tests were performed on various target cultures. Minimal inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The study of Elaeagnus angustifolia showed that the MCI (minimum inhibitory concentration) value of the fruit extract which indicates the antimicrobial activity against the targeted culture ranged from 7.5 mg/mL to 0.1 mg/mL. Above all, strong antimicrobial activity with MIC of 1.62 mg/ mL against E. coli was shown in this study [34]. The report signifies the presence of promising antimicrobial agents in the E. angustifolia fruit extracts.…”
Section: Antimicrobial Activitysupporting
confidence: 57%
See 2 more Smart Citations
“…The study of Elaeagnus angustifolia showed that the MCI (minimum inhibitory concentration) value of the fruit extract which indicates the antimicrobial activity against the targeted culture ranged from 7.5 mg/mL to 0.1 mg/mL. Above all, strong antimicrobial activity with MIC of 1.62 mg/ mL against E. coli was shown in this study [34]. The report signifies the presence of promising antimicrobial agents in the E. angustifolia fruit extracts.…”
Section: Antimicrobial Activitysupporting
confidence: 57%
“…During the recent years, due to the increased rate of illnesses caused by antibiotic-resistant microorganisms, the importance of using better alternatives such as medicinal plants with their natural antimicrobial activity has grown significantly [34].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Elaeagnus fruit and leaf extracts were both tested as antimicrobial agents on antibiotic-resistant microorganisms, showing good activity towards Escherichia coli and Salmonella typhimurium [17,18]. Finally, Elaeagnus polysaccharides were investigated for the best extraction conditions and their physicochemical and functional properties, and have been shown to exert anti-diabetic, antitumor, and immunological effects [19].…”
Section: Introductionmentioning
confidence: 99%